Fibonacci or Lucas numbers that are products of two Lucas numbers or two Fibonacci numbers - Daşdemir, Ahmet; Emin, Ahmet (arXiv, 2023)
This contribution presents all possible solutions to the Diophantine equations $F_k=L_mL_n$ and $L_k=F_mF_n$. To be clear, Fibonacci numbers that are the product of two arbitrary Lucas numbers and Lucas numbers that are the product of two arbitrary Fibonacci numbers are determined herein. The results under consideration are proven by using Dujella-Pethö lemma in coordination with Matveev's theorem. All common terms of the Fibonacci and Lucas numbers are determined. Further, the Lucas-square Fibonacci and Fibonacci-square Lucas numbers are given.
Keywords: Mathematics - Number Theory; FOS: Mathematics; Number Theory (math.NT); D61, 11J86, 11B39